Teachers' professional identities in the context of school-based sexuality education in Uganda—a qualitative study. Issue 6 (9th December 2020) - de Haas, Billie; Hutter, Inge
Abstract: School-based sexuality education makes teachers important gatekeepers of students' access to information about sexual and reproductive health and rights. The school setting has the potential to reach large numbers of students. However, teachers' professional identities may go beyond, differ from or even conflict with the qualities required of sexuality educators. To gain a better understanding of the role of professional identity in the delivery of school-based sexuality education, this study used cultural schema theory to study teachers' professional identities, and how these motivate them to provide sexuality education. In-depth interviews were conducted with 40 sexuality education teachers at secondary schools in Kampala, the capital of Uganda. Sexuality education lessons were observed to validate the findings from the interviews. Results identified five cultural schemas of professional identity: (i) upholder of ethics and regulations; (ii) authority figure; (iii) counsellor and guide; (iv) role model; and (v) guardian. The study concludes that teachers' cultural schemas of professional identity motivate them to adhere to moral discourses of abstinence and sexual innocence. To support teachers in taking more comprehensive approaches to sexuality education, it is important that they receive adequate teacher training and support from the Ugandan government, the school administration and the wider community.